Perfluorooctane sulfonate induces autophagy-dependent lysosomal membrane permeabilization by weakened interaction between tyrosinated alpha-tubulin and spinster 1. (November 2021) - Dong, Zhanchen; Qiu, Tianming; Zhang, Jingyuan; Sha, Shanshan; Han, Xiuyan; Kang, Jian; Shi, Xiaoxia; Sun, Xiance; Jiang, Liping; Yang, Guang; Yao, Xiaofeng; Ma, Yufang
Abstract: Perfluorooctane sulfonate (PFOS) is one kind of persistent organic pollutants. In previous study, we found that PFOS induced autophagy-dependent lysosomal membrane permeabilization (LMP) in hepatocytes, and siRNA against lysosomal permease spinster 1 (SPNS1) relieved PFOS-induced LMP. However, whether and how SPNS1 functioned as the link between autophagy and LMP was still not defined. In this study, we constructed a stable cell line expressing high levels of SPNS1. We found that SPNS1 interacted specifically with α-tubulin of tyrosinated isotype by pull-down assay. After treatment with PFOS, the level of tyrosinated α-tubulin was autophagy-dependently decreased. SPNS1-tyrosinated α-tubulin interaction was disrupted subsequently, which led to LMP eventually. We also found that stable high-expression of SPNS1 in hepatocytes accelerated lysosomal acidification, and deteriorated PFOS-induced LMP. This study pointed out that SPNS1-tyrosinated α-tubulin interaction mediated the cross-talk between autophagy and LMP induced by PFOS, shedding new light on the mechanism of PFOS hepatotoxicity. Graphical abstract: Image 1 Highlights: SPNS1 high-expression increases lysosomal acidification. SPNS1 high-expression aggravates PFOS-induced LMP. SPNS1-tyrosinated α-tubulin interaction mediates autophagy-LMP crosstalk.